Factors Influencing the Implementation of Project Risk Management in the South African Construction Industry - Masea, K.B.; Hassan, F.S.; Grobbelaar, S. (South African Journal of Industrial Engineering, 2025)
Effective project risk management is crucial for successful construction projects. However, the construction industry continues to face problems in implementing project risk management practices. This study investigates the barriers to and enablers of implementing project risk management in the South African construction industry. Semi-structured interviews of experienced industry professionals on a case study project were conducted to answer the research questions. The findings reveal that inadequate knowledge, communication breakdowns, financial constraints, and resistant attitudes are significant barriers to implementing project risk management. Conversely, leadership support, clear policies, and proactive engagement emerge as key enablers. A framework is proposed to address the barriers and to leverage the enablers, thus enhancing project risk management practices in the construction industry. This study contributes to the body of knowledge by providing actionable insights for construction organisations, policymakers, and stakeholders seeking to improve project outcomes through effective risk management.